Editorial: Frayed Careers: Exploring Rhythms of Working Lives. Issue 2 (20th February 2013) - Sabelis, Ida; Schilling, Elisabeth
Abstract : In studies on difference related to age and gender, we face 'abnormal' or 'typical' work‐life arrangements vis‐à‐vis taken‐for‐granted career concepts. Age and career are conceptualized from different angles depending on politics of work and organization, societal perspectives of age group position, perceived needs to have people work longer, and changing demographics. Underlying all this are questions of how age and gender are constituted in terms of their intersectional, dynamic relationship. We apply a perspective of rhythm to investigate what lies behind the linear life course and career perspectives. The notion of frayed careers serves to highlight rhythm and to criticize linearity and upward direction in views on careers, and at the same time calls for further theory development. In this introduction, we explore the implications of a dynamic‐rhythmic, yet 'frayed' perspective on life course, career and gender to represent stages of working life (lives) as interlinked and biographic.